Ciencia y Tecnología de la Información y del Conocimiento al Servicio de la Ingeniería - Medina García, Victor Hugo; Pérez Castillo, José Nelson; Torres Acosta, Jairo Humberto (Ingeniería, 2006)
The purpose of this paper shows the results of an investigation project developed in the Distrital University and that has allowed to gather the position of the foundations and limits for the definition and creation of an interdisciplinary investigation line that woultd sustain the implementation of a Doctorate in Engineering, covering the emphasis of their denomination fundamentally: ¨Science and technology of the information knowledge¨, which allows the interaction of different disciplines or investigation areas related to the services of the engineering, with the purpose of strengthening the academic and scientific development of the Distrital University Francisco José de Caldas Engineering Faculty in Colombia, which in spite of their wide trajectory and academic recognition, paradoxically suffers the lack of a program of doctoral formation that facilities and promotes the investigation in the field of the engineering.